2019
DOI: 10.3390/recycling4020014
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Ca- and Mg-Rich Fly Ash as a Chemical Precipitant in the Simultaneous Removal of Nitrogen and Phosphorus—Recycling and Reuse

Abstract: The European Union’s circular economy strategy aims to increase the recycling and re-use of products and waste materials. According to the strategy, the use of industry waste material should be more effective. A chemical precipitation method to simultaneously remove phosphorus and nitrogen from synthetic (NH4)2HPO4 solution and the liquid phase of anaerobic digestate using fly ash as a precipitant was tested. Fly ash is a waste material formed in the power plant process. It mainly contains calcium oxide (CaO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…However, there was a clear drop in the removal percentage at the end of the experiments. Therefore, the lengths of the experiments were reduced to 4-6 h. Others found that when calcined, powdered DOL [19] was used as a precipitation agent after being dissolved to water, the contact time needed was at least 24 h. The same finding was made with FA in another study [17]. This is due to the low solubility of MgO to water.…”
Section: Ammonium Removalmentioning
confidence: 89%
See 4 more Smart Citations
“…However, there was a clear drop in the removal percentage at the end of the experiments. Therefore, the lengths of the experiments were reduced to 4-6 h. Others found that when calcined, powdered DOL [19] was used as a precipitation agent after being dissolved to water, the contact time needed was at least 24 h. The same finding was made with FA in another study [17]. This is due to the low solubility of MgO to water.…”
Section: Ammonium Removalmentioning
confidence: 89%
“…The procedure used for the precipitation is based on previous studies [17,19]. Precipitation experiments were performed at room temperature (20°C ± 2°C) using different molar ratios Mg:P:N (1.1-2:1-2:1-2) and precipitation times (4-24 h).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations